Soldaten vor der Tür - die jüdische Gemeinde in Fürth im Spannungsverhältnis zwischen Militär und Obrigkeit = Soldiers at the Door - the Jewish Community in Tension between the Military and the Authorities - Strobel, Franziska (Aschkenas, 2023)
Quartering soldiers in private houses was still very prone to conflict in the 18th century. In the following article, I focus on this practice using the example of quartering during the Seven Years' War in the households of the inhabitants of Fürth, a market town near Nuremberg. Particular attention is primarily on the reaction and the opportunities for maneuver of the Jewish community and their efforts to free themselves from the quarterings between them and the Christian community and the Jewish community, respectively, as well as the divided local authorities. This conflict shows the way in which the religious and authoritarian boundaries functioned, and the extent they gave the individual actors room for action or limited it. A praxeological, actor-centered approach is employed to generate new insights into the conditions and manifestations of Jewish life.